Technician Section Repairing Information System Using Application on Smartphone: Case Study Phranakhon Si Ayutthaya Rajabhat University - Promrat, Thawatchai; khampha, Nanthawat (Kalasin University Journal of Science Technology and Innovation, 2023)
This research was conducted with the objective of developing an information system for informing maintenance of technicians for Phranakhon Si Ayutthaya Rajabhat University. The system is divided into two parts. As follows, the first part is for personnel who want to report repairs through an application on a smartphone. In this research, a smartphone application using the Flutter Framework and a web service was used to connect the application and the database. The second part is for maintenance personnel, which provides a web application developed using the Django Web Framework and using a PostgreSQL database to store data. The satisfaction assessment for 10 people who have used the information system was examined in this study. It is found that the level of satisfaction was very good with an average of 4.20 and a standard deviation of 0.51. In addition, the repair notification information system for the technician department facilitates personnel are able to report repairs and check the repair status through an application on a smartphone. Furthermore, maintenance department staff can manage information and provide repair services quickly, accurately and in a timely manner.